2021
DOI: 10.3390/pharmaceutics13060918
|View full text |Cite
|
Sign up to set email alerts
|

Imaging-Based Characterization of a Slco2b1(-/-) Mouse Model Using [11C]Erlotinib and [99mTc]Mebrofenin as Probe Substrates

Abstract: Organic anion-transporting polypeptide 2B1 (OATP2B1) is co-localized with OATP1B1 and OATP1B3 in the basolateral hepatocyte membrane, where it is thought to contribute to the hepatic uptake of drugs. We characterized a novel Slco2b1(-/-) mouse model using positron emission tomography (PET) imaging with [11C]erlotinib (a putative OATP2B1-selective substrate) and planar scintigraphic imaging with [99mTc]mebrofenin (an OATP1B1/1B3 substrate, which is not transported by OATP2B1). Dynamic 40-min scans were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(72 reference statements)
1
3
0
Order By: Relevance
“…2). This particular finding is in accordance with the assumption that erlotinib is a substrate of the human transporter (Bauer et al, 2018) and that OATP2B1 contributes to the hepatic uptake of the tyrosine kinase inhibitor in rodents and humans (Amor et al, 2018;Bauer et al, 2018;Marie et al, 2021). However, there was no change in the OSI-420/erlotinib ratio in the serum samples, suggesting that there is no difference in metabolism of erlotinib in our rat models.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…2). This particular finding is in accordance with the assumption that erlotinib is a substrate of the human transporter (Bauer et al, 2018) and that OATP2B1 contributes to the hepatic uptake of the tyrosine kinase inhibitor in rodents and humans (Amor et al, 2018;Bauer et al, 2018;Marie et al, 2021). However, there was no change in the OSI-420/erlotinib ratio in the serum samples, suggesting that there is no difference in metabolism of erlotinib in our rat models.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the tyrosine kinase inhibitor is a substrate of OATP2B1 (Bauer et al, 2018) and has previously been investigated in genetically modified mouse models. In a PET-study with [ 11 C]-erlotinib, mSlco2b1 À/À mice showed a reduced hepatic uptake clearance, however, with unchanged concentrations in blood (Marie et al, 2021). In another work, Li et al (2023) studied the pharmacokinetics of erlotinib and OSI-420 after oral administration in genetically modified mice.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, there are mOATP2B1-deficient mouse models available that have been investigated for the influence of the transporter on the in vivo disposition of erlotinib, fexofenadine, fluvastatin and rosuvastatin (Chen et al, 2020;Marie et al, 2021;Medwid et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, there are mOATP2B1‐deficient mouse models available that have been investigated for the influence of the transporter on the in vivo disposition of erlotinib, fexofenadine, fluvastatin and rosuvastatin (Chen et al, 2020; Marie et al, 2021; Medwid et al, 2019). Even though the murine data support a function of the transporter as a determinant of its substrates' pharmacokinetics by influencing oral absorption and hepatic clearance, there is still a need for further investigations including the impact of OATP2B1 on CP levels.…”
Section: Introductionmentioning
confidence: 99%